2014
DOI: 10.1152/ajpheart.00557.2014
|View full text |Cite
|
Sign up to set email alerts
|

An acute rise in intraluminal pressure shifts the mediator of flow-mediated dilation from nitric oxide to hydrogen peroxide in human arterioles

Abstract: Endothelial nitric oxide (NO) is the primary mediator of flow-mediated dilation (FMD) in human adipose microvessels. Impaired NO-mediated vasodilation occurs after acute and chronic hypertension, possibly due to excess generation of reactive oxygen species (ROS). The direct role of pressure elevation in this impairment of human arteriolar dilation is not known. We tested the hypothesis that elevation in pressure is sufficient to impair FMD. Arterioles were isolated from human adipose tissue and cannulated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 41 publications
8
54
2
Order By: Relevance
“…The potentiation was inhibited by tempol in the presence or absence of polyethylene glycol catalase (26), indicating a primary action of O 2 Ϫ rather than H 2 O 2 . Moreover, H 2 O 2 commonly acts as vasodilator in circulatory beds, such as cerebral, coronary, mesenteric, and skeletal muscle, and may function as an endotheliumdependent hyperpolarization factor and an activator of potassium channels (10,14,47,55,64,70); both dilator and hyperpolarizing actions are expected to blunt rather than potentiate pressure-induced myogenic constriction.…”
Section: Discussionmentioning
confidence: 99%
“…The potentiation was inhibited by tempol in the presence or absence of polyethylene glycol catalase (26), indicating a primary action of O 2 Ϫ rather than H 2 O 2 . Moreover, H 2 O 2 commonly acts as vasodilator in circulatory beds, such as cerebral, coronary, mesenteric, and skeletal muscle, and may function as an endotheliumdependent hyperpolarization factor and an activator of potassium channels (10,14,47,55,64,70); both dilator and hyperpolarizing actions are expected to blunt rather than potentiate pressure-induced myogenic constriction.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2 ml of fat tissue was removed and transferred to (48C) HEPES buffer solution. Following dissection, cannulation, and equilibration at physiological pressure and temperature, dilation of microvessels was observed via video microscopy, as described previously and in Supplementary material, http://links.lww.com/HJH/A617 [11,12,22,23]. After intraluminal pressure of 60 cm H 2 O was maintained for 30 min, vessels were constricted 30-50% with endothelin-1 (100-200 pmol final concentrations).…”
Section: Microvessel Flow-mediated Dilationmentioning
confidence: 99%
“…23 This was confirmed by two studies showing that in rat-isolated coronary arterioles 24 and mesenteric arteries, 22 cellular deformation induced by pressure, stretch and wall shear stress, potentiated the release of NO resulting in dilation, despite an increase in ROS production. However, Gutterman's group recently reported that in pressurized human peripheral arterioles, a severe increase in intravascular pressure for 30 min induced either ex vivo (in static conditions) 25 or in vivo (in pulsatile conditions), 26 promoted endothelial dysfunction evidenced by reduced eNOS-dependent NO activity and excessive ROS production. Therefore, both a lack of pulsatile pressure and its excess are damaging to the endothelium as they both impair NO-dependent dilations.…”
Section: Introductionmentioning
confidence: 99%